Multi-output DC-DC converters based on diode-clamped converters configuration: Topology and control strategy - Nami, A.; zare, F.; Ghosh, Arindam; Blaabjerg, F. (The Institution of Engineering and Technology, 2010)
This study presents a new DC–DC multi-output boost (MOB) converter which can share its total outputbetween different series of output voltages for low- and high-power applications. This configuration can be utilised instead of several single output power supplies. This is a compatible topology for a diode-clamed inverter in the grid connection systems, where boosting low rectified output-voltage and series DC link capacitors is required. To verify the proposed topology, steady-state and dynamic analyses of a MOB converter are examined. A simple control strategy has been proposed to demonstrate the performance of the proposed topology for a double-output boost converter. The topology and its control strategy can easily be extended to offer multiple outputs. Simulation and experimental results are presented to show the validity of the control strategy for the proposed converter.